The Influence of Moderate Physical Activity on Brain Monoaminergic Responses to Binge-Patterned Alcohol Ingestion in Female Mice - Buhr, Trevor J.; Reed, Carter H.; Shoeman, Allyse; Bauer, Ella E.; Valentine, Rudy J.; Clark, Peter J. (Frontiers in Behavioral Neuroscience, 2021)
Monoamine neurotransmitter activity in brain reward, limbic, and motor areas play key roles in the motivation to misuse alcohol and can become modified by exercise in a manner that may affect alcohol craving. This study investigated the influence of daily moderate physical activity on monoamine-related neurochemical concentrations across the mouse brain in response to high volume ethanol ingestion. Adult female C57BL/6J mice were housed with or without 2.5 h of daily access to running wheels for 30 days. On the last 5 days, mice participated in the voluntary binge-like ethanol drinking procedure, “Drinking in the dark” (DID). Mice were sampled immediately following the final episode of DID. Monoamine-related neurochemical concentrations were measured across brain regions comprising reward, limbic, and motor circuits using ultra High-Performance Liquid Chromatography (UHPLC). The results suggest that physical activity status did not influence ethanol ingestion during DID. Moreover, daily running wheel access only mildly influenced alcohol-related norepinephrine concentrations in the hypothalamus and prefrontal cortex, as well as serotonin turnover in the hippocampus. However, access to alcohol during DID eliminated wheel running-related decreases of norepinephrine, serotonin, and 5-HIAA content in the hypothalamus, but also to a lesser extent for norepinephrine in the hippocampus and caudal cortical areas. Finally, alcohol access increased serotonin and dopamine-related neurochemical turnover in the striatum and brainstem areas, regardless of physical activity status. Together, these data provide a relatively thorough assessment of monoamine-related neurochemical levels across the brain in response to voluntary binge-patterned ethanol drinking, but also adds to a growing body of research questioning the utility of moderate physical activity as an intervention to curb alcohol abuse.